No Calm After the Storm. A Decade of "The Tempest" in Polish Theatres (2012–2021) - Romanowska, Agnieszka (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The article discusses twelve productions based on The Tempest shown in Polish theatres in the years 2012-21, a decade whose challenges included escalation of the migration crisis, increasing climate change, social and political unrest around much of the globe, and the covid pandemic, but which was also marked by important Shakespearean anniversaries. In order to inspect the play’s significance for contemporary Polish audiences the productions are scrutinised in relation to four categories of interrelated issues: modification of characters, depiction of suspended reality connected with sleep, dreaming, memory and recollection, references to current social and political challenges, and employment of the play’s meta-artistic potential. The productions’ interpretative tendencies reveal a number of common denominators which are analysed with an aim of explaining why, in today’s Poland, the possibility of reconciliation and return to some form of re-established order that the playwright contemplates is seen as very difficult, if not impossible.